KESEJAHTERAAN RUMAH TANGGA PETANI PADI ORGANIK - Subikha, Ikha; Saidah, Zumi; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research was conducted on organic rice farmers in Krasak Village, which is an organic rice production center in Indramayu that has been certified by INOFICE. The hope of improving the welfare of organic rice farmers is often not fully achieved due to various factors, including cultivation methods that depend on chemicals and challenges in expanding farmers' knowledge and insight. The aim of this research is to evaluate the welfare of organic rice farmer households in Krasak Village, with a focus on aspects of basic needs, psychology, family development and self-actualization. This research used quantitative methods with a survey approach, conducted in Krasak Village, Jatibarang District, Indramayu Regency, West Java. Data were analyzed using descriptive analysis with a Likert scale, which involves the use of a criteria scale to determine scores based on a score level formula. It was found that organic rice farmers had quite positive perceptions regarding fulfilling basic family needs, psychological needs, family development and self-actualization. They have adequate access to food sources, clothing, decent housing conditions, and health services. However, there are challenges in maintaining good health and earning a stable income. Perceptions about family development and self-actualization show that there is room for improvement, especially in the aspects of social contribution and participation in society.